AIAA Atmospheric Flight Mechanics Conference and Exhibit 2006
DOI: 10.2514/6.2006-6144
|View full text |Cite
|
Sign up to set email alerts
|

Practical Aspects of the Equation-Error Method for Aircraft Parameter Estimation

Abstract: Various practical aspects of the equation-error approach to aircraft parameter estimation were examined. The analysis was based on simulated flight data from an F-16 nonlinear simulation, with realistic noise sequences added to the computed aircraft responses. This approach exposes issues related to the parameter estimation techniques and results, because the true parameter values are known for simulation data. The issues studied include differentiating noisy time series, maximum likelihood parameter estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 3 publications
2
92
0
1
Order By: Relevance
“…The computed error bounds from the FTR method accurately characterized these differences, which is consistent with similar findings in previous work [6,13]. Although such a measure is easy to compute postflight (when the converged values are known), metrics that can be computed in real time must be devised.…”
Section: Model Validitysupporting
confidence: 72%
See 1 more Smart Citation
“…The computed error bounds from the FTR method accurately characterized these differences, which is consistent with similar findings in previous work [6,13]. Although such a measure is easy to compute postflight (when the converged values are known), metrics that can be computed in real time must be devised.…”
Section: Model Validitysupporting
confidence: 72%
“…Explanations of why the estimated parameter standard errors are computed in this way, and why this calculation in the frequency domain produces parameter error measures that are consistent with the scatter in parameter estimates from repeated maneuvers, can be found in [6]. Realistic simulation testing has shown that the accuracy of model parameters estimated with this method is comparable to using a time-domain output-error method employing iterative nonlinear optimization in postflight analysis, for which all the data are available [13].…”
Section: B Real-time Parameter Estimation In the Frequency Domainmentioning
confidence: 80%
“…Because aircraft parameter estimation is often associated with data collinearity [25], a biased parameter estimation technique known as Principal Components Regression (PRC) was used. PCR is able to increase the accuracy of the parameter estimates in case of multi-collinearity among the predictor variables [20].…”
Section: Parameter Estimationmentioning
confidence: 99%
“…[1] provides a thorough description of this method (among others), along with information on how the method can be applied in practice and the MATLAB ® software that implements it. Using equation-error in the frequency domain has been shown 12 to produce modeling results comparable in accuracy to using iterative nonlinear optimization in a conventional output-error approach in the time domain, but requires much less computation and therefore is faster and easier to use. In fact, many of the modeling results presented here were computed in real time during the flight tests, using a real-time formulation of equation-error parameter estimation in the frequency domain 1,6,13 .…”
Section: Introductionmentioning
confidence: 99%